Study of component high cycle bending fatigue based on a new critical distance approach. (August 2019) - SongSong, Sun; MaoSong, Wan; Hui, Wang; Ying, Zhang; Mei, Xu Xiao
Abstract: In this article, high-cycle bending fatigue limit load prediction of several sets of high-strength steel crankshafts are conducted based on the critical distance (TCD)approach. Firstly, the critical length of the critical distance of the crankshaft is determined by the crack-modeling technique. Then the equivalent stress of the crankshaft is calculated by a combined method of the finite element and interpolation. Finally the fatigue limit load of the crankshaft with the same material but different structure is computed. Validation between the predictions and the experimental results shows that the conventional TCD may result in some errors in such fatigue limit load prediction, especially for the critical point method(the error may be larger than 10%). While the modified TCD proposed in this paper can provide a more satisfactory result in terms of the fatigue limit for a quick engineering prediction and is thus more suitable to be taken into the actual engineering applications. Graphical abstract: Unlabelled Image Highlights: Combination of the finite element analysis and fracture surface observation. Applying a new critical distance approach in component fatigue limit load prediction. Experimental verification for several cases and the universality of the conclusion can be improved obviously.